Liquidity and stock returns : empirical evidence in China - Lam, Pei Xin (2012)
We study how liquidity affects the cross-section of stock returns in China stock markets. Using the illiquidity measure of Amihud (2002), we document that stock returns are positively correlated with the lagged illiquidity, and negatively correlated with the contemporaneous illiquidity. When the stocks are sorted according to market types, we find that the impact of illiquidity on stock returns is most pronounced for the Growth Enterprise Market (GEM), followed by A-shares then, B-shares markets. Our results are qualitatively the same when stock turnover is used as an alternative measure of liquidity.